PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) DALAM PEMBUATAN BATIK JUMPUTAN UNTUK MENINGKATKAN KESADARAN SISWA TERHADAP BUDAYA LOKAL INDONESIA PADA KELAS II DI SDIT NABAWI - Aulia Zahra, Shirly; Kurnia, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Art education in elementary schools is often marginalized and lacks integration with local culture, causing students to be more familiar with popular culture than traditional arts. This study aims to describe the planning, implementation, and effectiveness of the Project Based Learning (PjBL) model in the making of jumputan batik to improve students’ awareness of Indonesian local culture in grade II of SDIT Nabawi. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving teachers and students. The results showed that the planning of PjBL was conducted systematically by integrating cultural values into learning objectives. The implementation of PjBL engaged students actively in designing motifs, selecting colors, and producing jumputan batik collaboratively. Furthermore, the application of PjBL proved effective in enhancing students’ understanding and positive attitudes toward local culture, as reflected in their enthusiasm, creativity, sense of pride, and appreciation of batik as a cultural heritage. Therefore, the PjBL model is considered effective and relevant for strengthening cultural awareness and creativity among lower-grade elementary school students.